Algorithmic Foundations of Robotics IX Selected Contributions of the Ninth International Workshop on the Algorithmic Foundations of Robotics - Hsu, David; Isler, Volkan; Latombe, Jean-Claude.; Lin, Ming C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Robotics is at the cusp of dramatic transformation. Increasingly complex robots with unprecedented autonomy are finding new applications, from medical surgery, to construction, to home services. Against this background, the algorithmic foundations of robotics are becoming more crucial than ever, in order to build robots that are fast, safe, reliable, and adaptive. Algorithms enable robots to perceive, plan, control, and learn. The design and analysis of robot algorithms raise new fundamental questions that span computer science, electrical engineering, mechanical engineering, and mathematics. These algorithms are also finding applications beyond robotics, for example, in modeling molecular motion and creating digital characters for video games and architectural simulation. The Workshop on Algorithmic Foundations of Robotics (WAFR) is a highly selective meeting of leading researchers in the field of robot algorithms. Since its creation in 1994, it has published some of the field’s most important and lasting contributions. This book contains the proceedings of the 9th WAFR, held on December 13-15, 2010 at the National University of Singapore. The 24 papers included in this book span a wide variety of topics from new theoretical insights to novel applications.
Homotopic Path Planning on Manifolds for Cabled Mobile Robots -- An Equivalence Relation for Local Path Sets -- Using Lie Group Symmetries for Fast Corrective Motion Planning -- Asynchronous Distributed Motion Planning with Safety Guarantees under Second-Order Dynamics -- Incremental Sampling-Based Algorithms for Open-loop Solutions of Pursuit-Evasion Games -- Multiagent Pursuit Evasion, or Playing Kabaddi -- Reconguring Chain-type Modular Robots Based on the Carpenter's Rule Theorem -- Robomotion: Scalable, Physically Stable Locomotion for Self- Recongurable Robots -- Adaptive Time Stepping in Real-Time Motion Planning -- The Bayes Tree: An Algorithmic Foundation for Probabilistic Robot Mapping -- Monte Carlo Value Iteration for Continuous State POMDPs -- Randomized Belief-Space Replanning in Partially-Observable Continuous Spaces -- GPU-based Parallel Collision Detection for Real-Time Motion Planning -- CCQ: Ecient Local Planning using Connection Collision Query -- Modeling Contact Friction and Joint Friction in Dynamic Robotic Simulation using the Principle of Maximum Dissipation -- Energy-based Modeling of Tangential Compliance in 3-Dimensional Impact -- Sampling-Diagrams Automata: A Tool for Analyzing Path Quality in Tree Planners -- Sucient Conditions for the Existence of Resolution Complete Planning Algorithms -- Grasp Invariance -- Path Planning on Manifolds using Randomized Higher-Dimensional Continuation -- Algorithms and Analytic Solutions using Sparse Residual Dipolar Couplings for High-Resolution Automated Protein Backbone Structure Determination by NMR: -- LQG-Based Planning, Sensing, and Control of Steerable Needles -- Goldberg Cyber Detectives: Determining When Robots or People Misbehave -- Gravity-Based Robotic Cloth Folding.
Keywords: Robotics; Automation; Artificial intelligence; Robotics and Automation; Artificial Intelligence